Response of wheat growth, grain yield and water use to elevated CO2 under a Free‐Air CO2 Enrichment (FACE) experiment and modelling in a semi‐arid environment. (6th February 2015) - O'Leary, Garry J.; Christy, Brendan; Nuttall, James; Huth, Neil; Cammarano, Davide; Stöckle, Claudio; Basso, Bruno; Shcherbak, Iurii; Fitzgerald, Glenn; Luo, Qunying; Farre‐Codina, Immaculada; Palta, Jairo; et al.
Abstract The response of wheat crops to elevated CO2 (eCO2) was measured and modelled with the Australian Grains Free‐Air CO2 Enrichment experiment, located at Horsham, Australia. Treatments included CO2 by water, N and temperature. The location represents a semi‐arid environment with a seasonal VPD of around 0.5 kPa. Over 3 years, the observed mean biomass at anthesis and grain yield ranged from 4200 to 10 200 kg ha−1 and 1600 to 3900 kg ha−1, respectively, over various sowing times and irrigation regimes. The mean observed response to daytime eCO2 (from 365 to 550 μmol mol−1 CO2) was relatively consistent for biomass at stem elongation and at anthesis and LAI at anthesis and grain yield with 21%, 23%, 21% and 26%, respectively. Seasonal water use was decreased from 320 to 301 mm (P = 0.10) by eCO2, increasing water use efficiency for biomass and yield, 36% and 31%, respectively. The performance of six models (APSIM‐Wheat, APSIM‐Nwheat, CAT‐Wheat, CROPSYST, OLEARY‐CONNOR and SALUS) in simulating crop responses to eCO2 was similar and within or close to the experimental error for accumulated biomass, yield and water use response, despite some variations in early growth and LAI. The primary mechanism of biomass accumulation via radiation use efficiency (RUE) or transpiration efficiency (TE) was not critical to define the overall response to eCO2. However, under irrigation, the effect of late sowing on response to eCO2 to biomass accumulation at DC65 was substantial in the observed data (~40%), but the simulated response was smaller, ranging from 17% to 28%. Simulated response from all six models under no water or nitrogen stress showed similar response to eCO2 under irrigation, but the differences compared to the dryland treatment were small. Further experimental work on the interactive effects of eCO2, water and temperature is required to resolve these model discrepancies.